Efficacy of photobiomodulation in reducing pain in cases of Tendonitis: A systematic review (International Seven Journal of Multidisciplinary, 2024)
Pain is a sensation that arises after potential or actual tissue damage, and can be classified as somatic or visceral, and often results from tissue damage common in inflammatory, traumatic, invasive or ischemic situations. Tendonitis is an inflammation resulting from mechanical overload or repetitive movements, generating inflammation and local pain. This study aims to review articles that report the efficacy of photobiomodulation on tendon pain and inflammation. Methodology: This is a systematic review study, carried out by searching articles in the following databases: Virtual Health Library, PubMed, Scielo and Revista Estima. National and international articles in Portuguese, English and Spanish were included. Conclusion: In this systematic review, it is concluded that the action of photobiomodulation reduces the inflammatory effects induced by thermal, chemical or mechanical actions, as in cases of tendinitis. Photobiomodulation inhibits the action peak generated by the lesion stimulus and by the signaling to the nociceptors, preventing the information of pain in the dorsal horn and promoting pain control. However, the need for further studies in this area is highlighted, as well as the standardization of time, dosage, and wavelength parameters to be used for a more effective treatment.